2019
DOI: 10.3389/fmicb.2019.01980
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Microbial Resistome in Conventional and “Raised Without Antibiotics” Beef and Dairy Production Systems

Abstract: Metagenomic investigations have the potential to provide unprecedented insights into microbial ecologies, such as those relating to antimicrobial resistance (AMR). We characterized the microbial resistome in livestock operations raising cattle conventionally (CONV) or without antibiotic exposures (RWA) using shotgun metagenomics. Samples of feces, wastewater from catchment basins, and soil where wastewater was applied were collected from CONV and RWA feedlot and dairy farms. After DNA extraction and sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 64 publications
10
68
1
Order By: Relevance
“…Similar levels of antimicrobial resistance were measured between conventional and "Raised Without Antibiotics" ground beef products (36) and beef cattle (37), which led to the doubt on the assumed impact of antimicrobial use in U.S. beef production and whether significant reductions in antimicrobial resistance could be yielded by reducing antimicrobial use. Although a recent study identified differences in resistomes between farms with different practices regarding antibiotic use (conventional versus "Raised Without Antibiotics"), the authors did not conclude a cause-effect relationship between antimicrobial use and the resistome differences because other factors (e.g., location, cattle source, management practices, and diet) could have affected the resistomes (38). It should be noted that our findings regarding the resistomes of ABF versus CONV samples were limited to finished chicken products.…”
Section: Discussionmentioning
confidence: 95%
“…Similar levels of antimicrobial resistance were measured between conventional and "Raised Without Antibiotics" ground beef products (36) and beef cattle (37), which led to the doubt on the assumed impact of antimicrobial use in U.S. beef production and whether significant reductions in antimicrobial resistance could be yielded by reducing antimicrobial use. Although a recent study identified differences in resistomes between farms with different practices regarding antibiotic use (conventional versus "Raised Without Antibiotics"), the authors did not conclude a cause-effect relationship between antimicrobial use and the resistome differences because other factors (e.g., location, cattle source, management practices, and diet) could have affected the resistomes (38). It should be noted that our findings regarding the resistomes of ABF versus CONV samples were limited to finished chicken products.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, lack of congruence between resistome and microbial communities in four dairy breeds suggested that other factors, in addition to antimicrobial use, might be associated with changes in resistome, and microbiome composition. It may also reflect the possibility that a small fraction of the total bacterial population was resistant to antibiotics (MacLean and Vogwill, 2015;Rovira et al, 2019), and that horizontal gene transfer disrupted the link between microbiome and resistome composition (Johnson et al, 2015). However, further investigations are necessary to evaluate the real effect of breed specific bacteria on cow mammary gland diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Non-host reads were then aligned to the MEGARes reference antimicrobial database (version 1.0.1) using the Burrows-Wheeler Aligner (BWA) with default settings 15 . Only antibiotic resistance determinants with gene fraction of >80% were identified as present in the sample and included for further analyses 4 , 5 , 16 . Each identified antibiotic resistance determinant was classified at the class-level using Resistome Analyzer ( https://github.com/cdeanj/resistomeanalyzer ).…”
Section: Methodsmentioning
confidence: 99%